Odpowiedź :
Odpowiedź:
3 i 8/11 - 4/11 = 3 i 4/11
5 i 13/15 - 8/15 = 5 i 5/15 = 5 i 1/3
6 i 6/7 - 2 i 4/7 = 4 i 2/7
12 i 8/9 - 9 i 5/9 = 3 i 3/9
3 i 3/7 - 5/7 = 2 i 10/7 - 5/7 = 2 i 5/7
1 i 3/11 - 7/11 = 14/11 - 7/11 = 7/11
4 i 1/6 - 2 i 5/6 = 3 i 7/6 - 2 i 5/6 = 1 i 2/6 = 1 i 1/3
18 i 7/13 - 6 i 10/13 = 17 i 20/13 - 6 i 10/13 = 11 i 10/13
Odpowiedź:
a)
3 8/11 - 4/11 = 3 4/11
b)
5 13/15 - 8/15 = 5 5/15 = 5 1/3
c)
6 6/7 - 2 4/7 = 4 2/7
d)
12 8/9 - 9 5/9 = 3 3/9 = 3 1/3
e)
3 3/7 - 5/7 = 2 10/7 - 5/7 = 2 5/7
f)
1 3/11 - 7/11 = 14/11 - 7/11 = 7/11
g)
4 1/6 - 2 5/6 = 3 7/6 - 2 5/6 = 1 2/6 = 1 1/3
h)
18 7/13 - 6 10/13 = 17 20/13 - 6 10/14 = 11 10/13
Szczegółowe wyjaśnienie: